Venous Thromboembolism in Children: The Rivaroxaban Experience - Spiezia, Luca; Campello, Elena; Tormene, Daniela; Simioni, Paolo (Seminars in Thrombosis and Hemostasis, 2024)
The incidence of venous thromboembolism (VTE) in the pediatric population has increased more than 10-fold in the last 20 years, as a consequence of the advancement of resuscitation and surgical techniques and the global increase in life expectancy of children suffering from chronic pathologies. Monitoring anticoagulant therapy to achieve outcomes within the target range in childhood VTE, parenteral administration of medications, and frequent blood tests in children are often cumbersome. Availability of safe and effective oral agents with pediatric data to support use would be of clear benefit. A physiologically based pharmacokinetic model was developed to estimate the appropriate dosing schedule for rivaroxaban in children. This incorporated growth/maturation and variability in anthropometrics (e.g., body height, weight, and body mass index), anatomy (e.g., organ weight), physiology (e.g., blood flow rates), metabolism and excretion. Rivaroxaban use in pediatric population underwent a complete investigational program, consisting mainly of one phase I pharmacokinetics/pharmacodynamics trial, three phase II trials, one phase III trial. The phase III trial enrolled 500 patients from birth to <18 years and documented the efficacy and safety of rivaroxaban regimens at dose equivalent to the adult 20 mg dose for the prevention of fatal or symptomatic nonfatal recurrent VTE and major bleeding versus heparin or vitamin K antagonists. Results were similar to those in rivaroxaban studies in adults. The efficacy and safety of rivaroxaban in children reported in the EINSTEIN JUNIOR trial provide further support to previous trials in adults (EINSTEIN Program), which demonstrate a favorable profile for the use of rivaroxaban for the management of VTE in challenging patient populations. Other clinical evidence contributing to the use of rivaroxaban among different risk groups in pediatric VTE population confirms the consistency with principal trial. Our review aims to describe the rationale for using rivaroxaban oral suspension in clinical practice and to summarize its multiple indications in each vascular bed (e.g., cerebral venous thrombosis, symptomatic or asymptomatic central venous catheter-associated thrombosis), etiology, and patients setting.
Keywords: venous thromboembolism; children; rivaroxaban